PENGARUH KEMAMPUAN INTELLECTUAL CAPITAL, PEMBERIAN REWARD DAN KEPUASAN KERJA TERHADAP KINERJA DOSEN STIE MUHAMMADIYAH MAMUJU DI KABUPATEN MAMUJU SULAWESI BARAT - Halim, Agus; Jusriadi, Edi (COMPETITIVENESS, 2020)
The performance of lecturers is reviewed from the Tri Dharma of Higher Education, namely education and teaching, research and community service. For teaching problems found the fact that the availability ofteaching is determined by the ability of lecturers to transfer knowledge in the form of writing. The presentation of information through textbooks, diktats, handouts, modules that clearly and systematically influence the process of information transfer. This study aims to find out how the influence of intellectual capital and rewarding the job satisfaction and performance of STIE Muhammadiyah Mamuju. This research was held at the Office of the Muhammadiyah Mamuju School of Economics using quantitative methods using data collection techniques through interviews, observations and questionnaires to human resources in this case is a lecturer of STIE Muhammadiyah Mamuju. The results of this study showed that: 1) There is a negative and insignificant influence between intellectual capital on the performance of STIE lecturer Muhammadiyah Mamuju. 2) There is a negative and insignificant influence between the reward to the performance of STIE lecturer Muhammadiyah Mamuju. 3) There is a positive and significant influence between job satisfaction on the performance of STIE lecturer Muhammadiyah Mamuju. 4) Job satisfaction is the dominant variable affecting the performance of STIE lecturer Muhammadiyah Mamuju. Keywords: Intellectual Capital, Reward, Job Satisfaction, Performance